The ammonia-Slc4a11 axis in T cells alleviates LPS-induced mastitis - Wu, Yuqing; Li, Zhi; Xi, Peiwen; Wang, Yaman; Guo, Haowei; Yin, Hong; Zhu, Lei (Frontiers in Immunology, 2025)
BackgroundMastitis is an inflammatory condition of the mammary gland, commonly observed in lactating and non-puerperal women, posing significant health and economic challenges. Lipopolysaccharide (LPS), a component of the outer membrane of Gram-negative bacteria, is a major inducer of mastitis. Ammonia, a key molecule in nitrogen metabolism, has been implicated in inflammatory pathways, yet its specific role in mastitis remains unclear. This study aims to investigate the mechanism by which ammonia influences the development of mastitis, particularly its effects on T cell activity and inflammatory factor expression.MethodsqRT-PCR and ELISA were performed to measure the levels of IL-6, TNF, and IL-1β in the breast tissue of mice with LPS-induced mastitis, with or without ammonia treatment. HE staining was used to evaluate the degree of inflammation in the mammary tissue. FACS analysis was employed to assess the percentage, viability, and proliferation of immune cells in the breast tissue. CRISPR-Cas9 technology was used to knockout the SLC4A11 gene in T cells.ResultsAmmonia treatment significantly alleviated LPS-induced mastitis by reducing inflammation and inflammatory factor levels. It also decreased the percentage of CD4+ and CD8+ T cells, inhibited T cell viability and proliferation, and reduced pro-inflammatory cytokine expression (TNF and IFN-γ). Knockdown of the ammonia transporter Slc4a11 in T cells exacerbated mastitis, suggesting that Slc4a11 regulates T cell activity and inflammation during the progression of mastitis.ConclusionIn summary, these findings highlight the critical role of ammonia and its transporter Slc4a11 in LPS-induced mastitis, providing potential therapeutic targets for future interventions.